Navigating climate change with bt corn: A study of efficiency in Philippine corn production - Jayme, Aphril Easter Sunday Jaemi Manuel; Lee, Yoonsuk (Asian Journal of Agriculture and Rural Development, 2025)
The Philippine corn industry, vital for national food security, faces significant threats from climate change. This study uses stochastic frontier analysis to assess climate’s impact on corn production efficiency from 1990 to 2020, focusing on the role of Bt corn adoption. Findings show that while higher temperatures and reduced rainfall increase production inefficiency, adopting Bt corn with fertilizer substantially mitigates these adverse effects. The 2002 commercialization of Bt corn marked a key turning point, reversing production declines and improving sector performance. These results underscore the need for climate-resilient agricultural strategies. Policy should prioritize irrigation expansion, improved rainfall utilization, broader access to crop insurance, and continued support for improved seed varieties like Bt corn. Strengthening these adaptive measures is crucial for enhancing the resilience and stability of the Philippine corn sector against ongoing climate challenges.